2015
DOI: 10.1155/2015/238529
|View full text |Cite
|
Sign up to set email alerts
|

Moving Clusters within a Memetic Algorithm for Graph Partitioning

Abstract: Most memetic algorithms (MAs) for graph partitioning reduce the cut size of partitions using iterative improvement. But this local process considers one vertex at a time and fails to move clusters between subsets when the movement of any single vertex increases cut size, even though moving the whole cluster would reduce it. A new heuristic identifies clusters from the population of locally optimized random partitions that must anyway be created to seed the MA, and as the MA runs it makes beneficial cluster mov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…In this study, a very simple clustering method [22] was used to find clusters that require large energy for movement. However, an improvement in its performance can be expected when more advanced clustering methods [7,21,24,25,26,27,28,29,30,31] are applied.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, a very simple clustering method [22] was used to find clusters that require large energy for movement. However, an improvement in its performance can be expected when more advanced clustering methods [7,21,24,25,26,27,28,29,30,31] are applied.…”
Section: Resultsmentioning
confidence: 99%
“…At present, designing approximate or heuristic algorithms that solve the problem is the only solution. There are also various meta-heuristic approaches to solving the graph bisection, including genetic algorithms [5,6,7] and tabu search [8,9]. Kim et al [10] present a survey of techniques using genetic algorithms.…”
Section: Graph Bisection and Testbedmentioning
confidence: 99%
See 1 more Smart Citation
“…The Fiduccia-Mattheyses algorithm [4] was used for local optimization and operators were revised to apply QEA. Hwang et al [5] demonstrated heuristic distinguishing clusters in the population of locally optimized random partitions. This becomes the seed of the memetic algorithm (MA), and once MA is executed, beneficial cluster moves can be performed.…”
Section: Local Search Algorithm In Hybrid Gasmentioning
confidence: 99%